Design of a device for lifting a Grand Piano - Henriques, Antonio Manoel Dias; Resende, Júlio Cesar Pesati; Alves, Augusto Brignol; de Morais, Davi Arruda; Junior, Eden Jose da Rocha; Tavares, Guilherme Pinheiro; Buss, Kelvin Rafael Paulino; Duarte, Leonardo Virginio de Assis; Vazquez, Marisa de Avila Rodriguez; Sforcini, Felipe Alves; Guimarães, Francisco Menezes; Moreira, Giovana Gonçalves; et al. (Seven Editora, 2024)
This article describes the process of designing a device to vertically elevate a grand piano together with the pianist. A device for this purpose has already been developed and applied in performances by the Swiss pianist Alain Roche abroad. The idea, with this project, is to do the same in Brazil, particularly in Brasilia, with the possibility, if there is interest, of expanding to other states. As the pianos, in order to be played, are positioned horizontally, it was necessary to adapt the action mechanism so that the piano could be played vertically. The project was developed within the scope of the discipline Project of Mechanical Systems of the Department of Mechanical Engineering of the University of Brasília – UnB and had the participation of thirteen students under the coordination of the professor of the discipline. Two types of devices have been developed, one that suits a particular grand piano that is being prepared for performances and another device that fits any grand piano, regardless of dimensions. The designed devices allow the pianist to be elevated vertically along with the piano comfortably and safely. Performances can be made outdoors or indoors that have the support of a lifting system to suspend the piano and the pianist. The project required an interdisciplinary approach, combining knowledge of mechanical engineering, ergonomics, music, safety and design, to ensure the technical and artistic feasibility of the device. DOI:https://doi.org/10.56238/sevened2024.026-025